115k views
2 votes
I need help with this equation
A(x+b)-c=d

1 Answer

3 votes
Reorder the terms:
a(b + x) + -1c = d
(b * a + x * a) + -1c = d
(ab + ax) + -1c = d

Solving
ab + ax + -1c = d

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add 'c' to each side of the equation.
ab + ax + -1c + c = c + d

Combine like terms: -1c + c = 0
ab + ax + 0 = c + d
ab + ax = c + d

Reorder the terms:
ab + ax + -1c + -1d = c + -1c + d + -1d

Combine like terms: c + -1c = 0
ab + ax + -1c + -1d = 0 + d + -1d
ab + ax + -1c + -1d = d + -1d

Combine like terms: d + -1d = 0
ab + ax + -1c + -1d = 0

There is no solution to this equation.
User Rich Murnane
by
4.9k points